Politics and Political Participation of “Grass-Roots” in General Election 2019, Bandar Selamat Regency, Medan, Indonesia - Rehia K. Isabella Barus; Armansyah Matondang; Nina Angelia; Beby Masitho Batubara (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Ahead of the 2019 general election which is divided into two stages, namely the Legislative election and the Presidential election. This event is the right moment to find out the political participation of the people at the grass-roots level while at the same time seeing the interaction between the people in the grass-roots and political parties. The interaction that wants to be seen is what forms of political behavior and community participation at the grassroots, as well as how political parties behave in interacting with this community. Then the important point that is also seen is how political parties behave in involving and seeking to raise support from the community. In the end, through this research, it will be known the quality of political participation from the public and electoral political parties in 2019.